Macro-regions in a process of national and regional development - Aranaga Manrique, David (2009)
Macro-regions emerge as a strategic instrument of the State whose purpose is to overcome the current centralism that prevails in the national productive system, as a result of the growth models and the evolutionary development of our society. Therefore, a new role of the State is required, in order to formulate plans and policies to promote a set of strategies around macro-regions, in the scenario of a process of change of national-regional development and the application of a “Development Model from the inside out”.